2019
DOI: 10.1093/infdis/jiz195
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Genetic Element Promotes the Association Between Serotype M28 Group A Streptococcus Isolates and Cases of Puerperal Sepsis

Abstract: Background Bacterial infections following childbirth—so-called puerperal infections—cause morbidity in 5%–10% of all new mothers. At low frequency, the infection can spread to the blood, resulting in life-threatening sepsis known as puerperal sepsis. Pathogens causing puerperal sepsis include group A Streptococcus (GAS), and epidemiological analyses have identified isolates of a single serotype, M28, as being nonrandomly associated with cases of puerperal sepsis. The genomes of serotype M28 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The many diseases caused by GAS differ dramatically in their clinical presentation and lethality. Additional layers of variability are observed due to strain‐ and serotype‐specific differences in the ability of isolates to cause distinct diseases, with molecular mechanisms such as the modulation of regulatory systems, or gene gain/loss, accounting for such variation (Cao et al , ; Sarkar and Sumby, ; Jain et al , ; Kachroo et al , ). At the center of strain‐ and serotype‐specific variability in GAS disease potential is the CovR/S two‐component system.…”
Section: Discussionmentioning
confidence: 99%
“…The many diseases caused by GAS differ dramatically in their clinical presentation and lethality. Additional layers of variability are observed due to strain‐ and serotype‐specific differences in the ability of isolates to cause distinct diseases, with molecular mechanisms such as the modulation of regulatory systems, or gene gain/loss, accounting for such variation (Cao et al , ; Sarkar and Sumby, ; Jain et al , ; Kachroo et al , ). At the center of strain‐ and serotype‐specific variability in GAS disease potential is the CovR/S two‐component system.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that deletion of the entire RD2 region conferred decreased ability of an M28 GAS strain to adhere in vitro to immortalized human vaginal epithelial cells and to colonize the female genital tract in a mouse model of infection. 70 Our screen did not identify genes in the RD2 region as contributing factors for GAS colonization in this NHP female genital tract infection model. At least three possibilities may explain this observation.…”
Section: Discussionmentioning
confidence: 68%
“…They also express one collagen-binding protein, Epf, in addition to the shared pilus and SpyAD (40). Finally, RD2, a 32 kb DNA region quasi specific to emm28 strains modify, via encoded virulence factors and regulators, the virulence potential of emm28 strains, contributing to their association with puerperal fever (41). The composition of the decidua surface and all these factors may explain the capacity of GAS to adhere to this tissue, a critical step in invasive puerperal fever.…”
Section: Discussionmentioning
confidence: 99%